2021
DOI: 10.1016/j.asmr.2021.09.010
|View full text |Cite
|
Sign up to set email alerts
|

The Proximal Tibia Loses Bone Mineral Density After Anterior Cruciate Ligament Injury: Measurement Technique and Validation of a Quantitative Computed Tomography Method

Abstract: Purpose To develop a standardized method for tibial tunnel volumetric bone mineral density (BMD) analysis with quantitative computed tomography (qCT) using cadaveric specimens to provide validation of this technique on a healthy control population and to determine whether osteopenia occurs following an anterior cruciate ligament (ACL) injury. Methods: qCT was used to develop a volumetric BMD (mg/cm 3 ) measurement technique throughout the region of a standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Overall, this study demonstrated that patient findings of significant osteoclast activity 33,41 are reproduced in our in vivo rodent model, despite a locomotive difference between the 2 species and that the majority of ACL injuries in our model were partial in nature. Although we did not confirm our hypothesis, we demonstrated that the presence of osteoclast activity within the mineralized matrices in response to injury was associated with a significant reduction in bone volume by 28 days in both condylar and entheseal regions.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Overall, this study demonstrated that patient findings of significant osteoclast activity 33,41 are reproduced in our in vivo rodent model, despite a locomotive difference between the 2 species and that the majority of ACL injuries in our model were partial in nature. Although we did not confirm our hypothesis, we demonstrated that the presence of osteoclast activity within the mineralized matrices in response to injury was associated with a significant reduction in bone volume by 28 days in both condylar and entheseal regions.…”
Section: Discussionmentioning
confidence: 52%
“…Analyses of their ACL entheseal tissue, removed during ACLR bone tunneling, found significant catabolic activity in patients ~4 to 7 weeks after injury, compared with age-matched cadaveric controls. Recently, a complementary study conducted by Marigi et al 33 found a similar phenomenon within the tibial tunnel of patients with an ACL injury compared with a comparable tunnel region analyzed in their contralateral knee and a cohort of healthy individuals. However, neither study investigated the bone outside of the tunnel region, so it remains unknown if ACL entheseal bone loss is different from global loss bone that occurs across the injured joint.…”
mentioning
confidence: 70%
See 2 more Smart Citations